2018
DOI: 10.1158/1535-7163.mct-17-1148
|View full text |Cite
|
Sign up to set email alerts
|

We're Not “DON” Yet: Optimal Dosing and Prodrug Delivery of6-Diazo-5-oxo-L-norleucine

Abstract: The broadly active glutamine antagonist 6-diazo-5-oxo-L-norleucine (DON) has been studied for 60 years as a potential anticancer therapeutic. Clinical studies of DON in the 1950s using low daily doses suggested antitumor activity, but later phase I and II trials of DON given intermittently at high doses were hampered by dose-limiting nausea and vomiting. Further clinical development of DON was abandoned. Recently, the recognition that multiple tumor types are glutamine-dependent has renewed interest in metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
178
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 176 publications
(184 citation statements)
references
References 65 publications
5
178
1
Order By: Relevance
“…DON as an anti-tumor agent has been studied for 60 years. While DON treatment resulted in some encouraging responses in phase I and II clinical trials in the 1950s to the 1980s, the development of DON was limited by its GI toxicity (Ahluwalia et al, 1990;Lemberg et al, 2018). Our novel compound, JHU083, limits toxicity by creating an inert prodrug that is preferentially (though not exclusively) converted to the active compound DON within the TME (Lemberg et al, 2018;Rais et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DON as an anti-tumor agent has been studied for 60 years. While DON treatment resulted in some encouraging responses in phase I and II clinical trials in the 1950s to the 1980s, the development of DON was limited by its GI toxicity (Ahluwalia et al, 1990;Lemberg et al, 2018). Our novel compound, JHU083, limits toxicity by creating an inert prodrug that is preferentially (though not exclusively) converted to the active compound DON within the TME (Lemberg et al, 2018;Rais et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…While DON treatment resulted in some encouraging responses in phase I and II clinical trials in the 1950s to the 1980s, the development of DON was limited by its GI toxicity (Ahluwalia et al, 1990;Lemberg et al, 2018). Our novel compound, JHU083, limits toxicity by creating an inert prodrug that is preferentially (though not exclusively) converted to the active compound DON within the TME (Lemberg et al, 2018;Rais et al, 2016). It is important to note, that while we can evaluate the efficacy of our approach in mice, we cannot evaluate the toxicity and pharmacokinetics in small animals (rodents) because they metabolize the prodrugs differently than humans (Rais et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The dose for DON used in these studies ranged from 50mg/m 2 -480mg/m 2 . The lowest dose used (50mg/m 2 ) translates to roughly 6mg/kg in mice (35,38,73). However, DON was never evaluated as a sensitizing agent for immune therapy in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…With the recent knowledge that tumor microenvironment is an integral component that drives progression of the tumors, there has been a renewed interest in reviving DON as an anti-tumor agent. Since recent evidence showed that a broad-spectrum antagonist of glutamine is more effective in inducing tumor regression than selective inhibition of a single glutamine-utilizing enzyme (36), DON is being re-evaluated as a potential therapy in a number of cancers specifically in combination with other chemotherapeutic agents (37,38). Therapeutic strategies using DON against glutamine dependent tumors have also been proposed (38).…”
Section: Introductionmentioning
confidence: 99%
“…The glutamine dehydrogenase inhibitor, epigallocatechin gallate (EGCG) is also proposed to target glutamine metabolism through an effect on glutamate dehydrogenase (207). The glutaminase inhibitor, 6-diazo-5oxo-L-norleucine (DON), is a powerful glutamine-targeting drug that can work synergistically with a restricted KD for managing brain cancer and metastasis (60,208,209). Hence, KMT can, (a), target the multiple drivers of rapid tumor growth, (b), facilitate drug delivery to the tumor tissue, (c), work synergistically with glutamine-targeting drugs, and, (d), enhance the metabolic efficiency in normal healthy cells.…”
Section: Ketogenic Metabolic Therapymentioning
confidence: 99%